Bone density in women receiving depot medroxyprogesterone acetate for contraception. Issue 6793 (6th July 1991) - Cundy, T; Evans, M; Roberts, H; Wattie, D; Ames, R; Reid, I R
Abstract : OBJECTIVE--To determine if the use of the injectable contraceptive depot medroxyprogesterone (DMPA), which reduces ovarian oestrogen production, is associated with changes in bone density. DESIGN--Population study. DMPA users were compared with two control groups selected from larger population studies and individually matched for several putative determinants of bone density (age, race, body mass index, and years of oestrogen deficiency). Controls and DMPA users were matched without prior knowledge of their bone density measurements. SETTING--Teaching hospital and community family planning clinics. SUBJECTS--30 current users of DMPA with a minimum five years' previous use, 30 premenopausal controls, and 30 postmenopausal controls. MAIN OUTCOME MEASURE--Lumbar spine and femoral neck bone mineral density assessed by dual energy x ray absorptiometry. RESULTS--Compared with premenopausal controls matched for age, race, and body mass index, DMPA users had significantly reduced bone density in the lumbar spine (mean difference 7.5% (95% confidence interval 1.9% to 13.1%), p = 0.002) and in the femoral neck (6.6%, (0.8% to 12.3%), p = 0.007). Compared with postmenopausal controls matched for body mass index and duration of oestrogen deficiency, DMPA users had greater bone density in the lumbar spine (8.9% (4.3% to 13.5%), p = 0.001), but in the femoral neck the difference in bone density was less (4.0% (-0.4% to 8.5%), p = 0.04). CONCLUSIONS--Women using DMPA have bone density values intermediate between those of normal premenopausal and postmenopausal controls; thus, the degree of oestrogen deficiency induced by DMPA may have an adverse effect on bone density.